Considerations and Guidance for the Structure, Organisation, and Operation of Cardiometabolic Prevention Units: A Consensus Statement of the Inter-American Society of Cardiology - Carlos I. Ponte-Negretti; Fernando Stuardo Wyss; Daniel Piskorz; Álvaro Sosa Liprandi; Alberto Lorenzatti; Livia Machado; Patricio López-Jaramillo; Eduardo Barbosa; José R. Gómez-Mancebo; Ricardo López; Osiris Valdez; Leonardo Cobos; et al. (Ubiquity Press, 2021)
Cardiovascular diseases (CVDs) remain the leading cause of death worldwide, particularly in low- and middle-income regions such as Latin America. This is because of the combination and interaction in different proportions of a high prevalence of cardiometabolic risk factors and socio-economic and cultural characteristics. This reality brings about the need to change paradigms to consistently and systematically boost cardiovascular prevention as the most cost-effective medium- to long-term strategy to reduce their prevalence in medium- and low-resource countries, not only in Latin America but also in other global regions. To achieve the therapeutic goals in various diseases, including CVD, the current literature demonstrates that the most effective way is to carry out the patient's diagnosis and treatment in multidisciplinary units. For this reason, the Inter American Society of Cardiology (IASC) proposes the creation of cardiometabolic prevention units (CMPUs) as a regional initiative exportable throughout the world to standardise cardiovascular prevention based on the best available evidence. This ensures homogeneity in the global management of cardiometabolic risk factors and access to quality medicine independently of the population's social situation. These guidelines, written by a panel of experts in cardiovascular prevention, defines what a CMPU is, its objectives and the minimum requirements for it, as well as proposing three categories and suggesting an operational scheme. It must be used as a guide for all individuals or centres that, aware of the need for multidisciplinary and standardised work, want to create a unit for the comprehensive management of cardiometabolic risk established as an international research network. Lastly, the document makes meaningful points on the determination of cardiovascular risk and its importance. These guidelines do not cover specific targets and therapeutic schemes, as these topics will be extensively discussed in another SIAC publication, namely a statement on residual cardiometabolic risk.